Analysis of socio demographic economic components in the livelihood vulnerability index of coastal communities due to tidal flooding in Bandar Lampung City - Putri, Resha Moniyana; Gunarto, Toto; Husaini, Muhammad; Irham, Ahmad Rowatul (Privietlab, 2026)
Tidal flooding is a recurring hazard in coastal areas and poses a serious threat to the sustainability of community livelihoods, particularly in regions that are highly dependent on coastal-based economic activities. In Bandar Lampung City, frequent tidal flooding events have disrupted the social, demographic, and economic conditions of coastal households, increasing their overall livelihood vulnerability. This study aims to analyze the level of social demographic economic vulnerability of coastal communities using the Livelihood Vulnerability Index (LVI) approach. The assessment focuses on four coastal districts Bumi Waras, Panjang, Teluk Betung Timur, and Teluk Betung Selatan and applies a balanced weighted averaged method to ensure equal contribution of each indicator within the composite index. Standardization of sub-components is conducted to enable consistent aggregation and comparison across districts. The results reveal that all studied districts fall within the vulnerable to very vulnerable categories. Bumi Waras District shows the highest level of vulnerability, primarily driven by a high proportion of female-headed households and limited household expenditure capacity. Panjang District is also characterized by considerable vulnerability due to demographic pressures and reduced labor productivity associated with household age structure. Meanwhile, Teluk Betung Timur and Teluk Betung Selatan exhibit relatively lower vulnerability levels, although persistent dependency ratios and gender-related household characteristics continue to constrain resilience. These findings demonstrate that livelihood vulnerability in coastal urban areas is multidimensional and shaped by the interaction of demographic structure, gender roles, and economic capacity. The study highlights the importance of integrating social and economic dimensions into coastal development planning and disaster risk reduction efforts to enhance household resilience and support sustainable livelihoods in Bandar Lampung City.